PENINGKATAN KEMAMPUAN GURU-GURU PRAKARYA SMP KOTA SOLOK SEBAGAI UPAYA MENGATASI PERMASALAHAN PEMBELAJARAN KERAJINAN - abd hafiz; Nessya Fitryona; Efrizal Efrizal; Suib Awrus (Ranah Seni, 2018)
One of the material in craft subjects is craft. The problem is the craft teachers in Junior High School in Solok are generally not from a craft / art education background. Even though one of the material in craft subjects is craft. For teachers who do not have art and craft education backgrounds, it is difficult to carry out craft learning, because they do not master the material. These problems need to be solved. The solution offered to solve the above priority problems is to improve the teacher’s ability by carrying out training activities for them. This activity was done by counseling methods and training in making crafts and designing learning strategies. The results of this activity are; 1) generally, the teachers are able to make good crafts, especially making makrame and woven crafts and 2) generally, the teachers are able to design learning strategies well.